THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN EDUCATION - Risova Galiya Baybulatovna (Galaxy International Interdisciplinary Research Journal, 2024)
The rapid development of technology has revolutionized various aspects of human life, including education. Modern pedagogical technologies are playing a decisive role in turning traditional classrooms into dynamic and interactive learning environments. This article explores the impact of these technologies on education, discussing their benefits, challenges, and future prospects. Key areas of focus include online learning platforms, virtual reality, gamification, adaptive learning systems, and artificial intelligence. The integration of these technologies has the potential to increase student engagement, individualize instruction, and develop critical thinking skills. At the same time, serious attention should be paid to addressing issues related to accessibility, privacy and the digital divide. As education continues to evolve, the effective integration of modern pedagogical technologies offers great prospects for creating innovative and inclusive learning experiences.